UNLOCKING ORGANIZATIONAL SUCCESS: LEVERAGING FINANCIAL STATEMENT ANALYSIS AS A PROFOUND TOOL FOR ASSESSING PROFIT PERFORMANCE - Hasanah, Rifka Marifatul; Suib, Mohammad (Universitas Nurul Jadid, 2023)
This research aims to analyze the financial performance of non-profit organizations. The method used is a qualitative type of literature approach, namely by comparing and evaluating concepts obtained from documents in the form of profit organization financial report data and references from books, journals, magazines and financial data from official websites of profit organizations. The results of this research can be calculated as GPM NPM. ROA and ROE. An organization's financial condition can be said to be by OJK standards if it meets the criteria for profitability ratios in profit organizations. In the 2018-2022 period, profit organizations experienced fluctuations in financial performance in the profitability aspect. This can be seen based on the calculation of ROA, ROE, and NPM over the last five years; namely, the average data obtained is ROA of 0.02%, ROE of 0.48%, NPM of 4.94%, and GPM of 0.9%. This data shows that profit organizations still need to meet the financial performance assessment standards set by Bank Indonesia.